Eko-Teologi Al-Qur’an dalam Perspektif Teori Ḥudūd Muhammad Syahrur: Kajian atas QS. Al-A‘rāf Ayat 31 dan 56–58 serta QS. Ar-Rūm Ayat 41 - Ahmad Miraji (Faculty Ushuluddin, Adab, and Dakwah Institut Agama Islam Negeri (IAIN) Palangka Raya, 2026)
The contemporary environmental crisis reflects an imbalance in the relationship between humans and nature, characterized by excessive exploitation of natural resources, pollution, deforestation, and various forms of ecological degradation. This study aims to analyze the Qur’anic principles of eco-theology contained in Q.S. Al-A‘rāf verses 31 and 56–58 and Q.S. Ar-Rūm verse 41 through the perspective of Muhammad Syahrur’s theory of ḥudūd. This research employs a qualitative-descriptive library research method using thematic interpretation, eco-theology, and linguistic-semantic approaches. The findings reveal that these Qur’anic verses construct an ecological ethic based on three main concepts: isrāf as the act of exceeding proper limits, fasād as the manifestation and consequence of ecological destruction, and iṣlāḥ as the effort to preserve, restore, and maintain environmental balance. From the perspective of the theory of ḥudūd, human beings are granted the freedom to utilize natural resources; however, such freedom is not absolute and must remain within boundaries that do not damage ecological carrying capacity or the regenerative ability of nature. Thus, humans should not be regarded as absolute owners of nature, but rather as trustees responsible for sustaining life. This study concludes that the theory of ḥudūd can be developed as a relevant ethical framework for criticizing excessive exploitation and promoting proportional, just, and sustainable environmental management.